Assessment of Extension Agents’ Perception of Mobile Phone Usage for Communication with Farmers in EDO South of EDO State, Nigeria - Alakpa, S. O. E.; Afolabi, S. O.; Ighalo, I. J. (International Journal of Environment, Agriculture and Biotechnology, 2019)
The use of mobile phones as means of communication between the extension agents and local farmers in Edo South was examined to determine the perception of the extension agents on its effectiveness. Fifty-one (51) respondents were obtained through random sampling using questionnaires to obtain relevant information in the two local government areas; Ovia North East and Ovia South West selected for the study. The result obtained indicated that male extension agents were in majority (72.5%), 54.9% of the sampled population above 45 years of age and 58.8% possesed 16 – 20 years working experience. Phone calls and short message service (SMS) were found appropriate for agricultural information dissemination. Significant and positive relationship were established between the working experience of extension agents and their perception of mobile phone usage. The recommendation is that formal integration of mobile phone into extension activities be done to enhance wider coverage, reduce cost and risks associated with movement. Extension agents and farmers need more training on effective usage of SMS and phone calls for interaction on farm related issues. Enforcement of existing telecommunication laws could reduce network failure and also enhance effective usage.